(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The adolescent period is the most crucial period, since the foundations of morality are formed here, social attitudes, attitudes towards oneself, people, and society are formed. In addition, at this age, character traits and basic forms of interpersonal behavior are stabilized. All these qualities develop in the process of communication between a teenager and people. Communication is becoming the leading activity of a teenager. Communication plays a very significant role in the formation and development of self awareness, and the correct image of "I" is formed in a child only when the people around him are sincerely interested in it. The article examines the features of the development of interpersonal relationships in adolescents. The results of the study of the development of two motives are presented: the desire for people, the fear of being rejected, three possible "types" of perception by the individual of the group are identified.